Studi Perkembangan Motorik Kasar Siswa Sekolah Dasar Negeri dan Swasta di Kota Bandung - Muhamad Nasrul; Mochamad Ridwan; Muchamad Arif Al Ardha (Jurnal Porkes, 2026)
This study was motivated by the importance of gross motor development as the foundation for physical activity in elementary school students, but it was suspected that there were differences in the quality of these abilities between public and private school students. The purpose of this study was to analyze the differences in gross motor skills between third-grade students in public and private elementary schools in Bandung. The method used was descriptive comparative with a quantitative approach. The research sample consisted of 38 students selected purposively, divided into 19 students from public schools and 19 from private schools. Data collection used the Gross Motor Development-2 (TGMD-2) test instrument, which measures locomotor and object control aspects. Data analysis was performed using the Shapiro-Wilk normality test, the independent sample t-test for normal data, and the Mann-Whitney test for non-normal data. The results showed that there was a significant difference in gross motor skills between the two groups. Private school students had better abilities in locomotor aspects (M=10.58 vs 8.68; p=0.006) and object control (p=0.018). The conclusion of the study indicates that PJOK learning factors, school environment, and availability of supporting facilities influence students' gross motor development.